Lactobacillus johnsonii BS15 combined with abdominal massage on intestinal permeability in rats with nonalcoholic fatty liver and cell biofilm repair. Issue 1 (1st January 2021) - Zhang, Wei; Li, Huanan; Zhao, Na; Luo, Xiongfei; Liu, Siwen; Bao, an; Chen, Yingying; Wang, Haiteng; Wang, Junshi; Wang, Jingui
ABSTRACT: This study aimed to analyze the effect of lactobacillus johnsonii BS15 (isolation of homemade yogurt from Ahu Hongyuan Grassland) combined with abdominal massage on intestinal permeability in rats with nonalcoholic fatty liver disease (NAFLD) and cell biofilm repair. Forty-five rats were divided randomly into five groups, four of which were fed with high-fat diet to establish NAFLD models. According to the treatment methods, they were grouped into group A (lactic acid bacteria feeding), group B (abdominal massage), group A + B (a combination of the two methods), model group (distilled water feeding), and normal group (distilled water feeding). Then, the pathological indexes of liver and intestinal permeability were observed. FITC-Dextran content of the model group elevated markedly compared with normal group ( P < 0.01), indicating that the intestinal permeability of NAFLD rats fed with high-fat diet increased. The intestinal permeability of groups A, B, and A + B was lower sharply than that of model group ( P < 0.01), and the effect of group A + B was the most obvious. HE staining of liver tissues showed that combined treatment could improve structural changes in liver cells caused by modeling and restore the normal structure of intestinal cells. Lactobacillus combined with abdominal massage was better than two treatments alone, further promoting the permeability of intestinal mucosa in NAFLD rats and repair biofilm of hepatocytes. The results initially verified the intervention effect of abdominal massage on intestinal mucosal permeability, and further revealed the mechanism of abdominal massage in treatment of NAFLD by improving intestinal mucosal barrier permeability. Graphical abstract: uf0001